Land Use Changes and Their Effects on the Value of Ecosystem Services in the Small Sanjiang Plain in China - Jing Chen; Bo-Ming Sun; Dan Chen; Xin Wu; Long-Zhu Guo; Gang Wang (The Scientific World Journal)
The small Sanjiang plain is one of the most important commodity grain production bases and the largest fresh water wetland in China. Due to the rapid expansion of agricultural activities in the past 30 years, the contradiction between economic development and the loss of ecosystem services has become an issue of increasing concern in the area. In this study, we analysed land use changes and the loss of ecosystem services value caused by these changes. We found that cropland sprawl was predominant and occurred in forest, wetland, and grassland areas in the small Sanjiang plain from 1980 to 2010. Using a model to evaluate ecosystem services value, we calculated that the decreased values of ecosystem services were 169.88 × 108 Yuan from 1980 to 2000 and 120.00 × 108 Yuan from 2000 to 2010. All of the ecosystem services were diminished from 1980 to 2010 except for food production. Therefore, the loss of ecosystem services value should be considered by the policymakers of land use and development.